Increased in Soil and Water Phospate in Peat Ponds Treared with a Mixture of Biologycal Fertilizers - Bagus Aprianto; Saberina Hasibuan; Syafriadiman syafiadiman (Faculty of Fisheries and Marine, Universitas Riau, 2022)
This research was conducted on November until December 2019, on Peatlands, Kualu Nenas Village, Tambang District, Kampar Regency, Riau Province. The aim of this research was to determine the effect of giving a mixture of human and cow feces biological fertilizers and to get the best comparison of a mixture of human and cow feces biological fertilizers on the increase in soil phosphate and peat pond water. The method of this research is an experimental method using a Complete Random Design (CRD) with one factor, six treatments, and three replications is P0: Control, P1: 100% giving of cow feces (120g), P2: 25% giving of human feces (30g) + 75% cow feces (90g), P3: 50% human feces (60g) + 50% cow feces (60g), P4: 75% human feces (90g) + 25% cow feces (30g), and P5: 100% human feces (120g). The results showed that 75% giving of human feces (90g) + 25% giving of cow feces biological fertilizers (30g) had an effect on phosphate changes in soil and peat water media with the respective levels obtained at 0,47% - 0,74% and phosphate content of water is 1,37 ppm-3,50 ppm.